Experience of patent ductus arteriosus ligation during extracorporeal membrane oxygenation treatment in newborns with severe respiratory failure due to persistent pulmonary hypertension: a single-center retrospective study - Qi-Liang Zhang; Yi-Nan Liu; Ya-Ting Zeng; Yi-Rong Zheng; Qiang Chen (Italian Journal of Pediatrics)
Abstract Background The aim of this study is to summarize our center’s experience with patent ductus arteriosus (PDA) ligation during extracorporeal membrane oxygenation (ECMO) treatment in newborns with severe respiratory failure due to persistent pulmonary hypertension of the newborn (PPHN). Methods We retrospectively collected and analyzed clinical data from five newborns with severe respiratory failure due to PPHN who underwent PDA ligation during ECMO treatment at our hospital between January 2021 and August 2023. Results All five patients had large PDAs, measuring 10 mm, 6 mm, 6 mm, 7 mm, and 6 mm, respectively. Significant left-to-right shunting through the PDA was observed after 29 h, 14 h, 3 h, 7 h, and 5 h of ECMO treatment, respectively, at which point successful PDA ligation was performed. The surgical durations were 52 min, 45 min, 55 min, 50 min, and 40 min, respectively. Post-ligation, blood lactate levels significantly decreased compared to preoperative values. Four patients were successfully weaned off ECMO, with ECMO support durations of 64 h, 92 h, 70 h, and 87 h, respectively. After ECMO removal, mechanical ventilation was discontinued after 5.2 days, 7.2 days, 9.5 days, and 5.5 days, respectively. None of the four surviving patients experienced complications such as residual shunting, bleeding, chylothorax, neurologic injury, pneumothorax, poor wound healing, or sepsis. Conclusion During ECMO treatment for PPHN in newborns with large PDAs, the direction of blood flow through the PDA should be closely monitored. PDA ligation is a feasible and reasonable intervention when pulmonary artery pressure decreases and left-to-right shunting through the PDA becomes evident.